The physiological basis of complementary and alternative medicines for polycystic ovary syndrome - Raja-Khan, Nazia (Am J Physiol Endocrinol Metab, 2011)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder that is characterized by chronic hyperandrogenic anovulation leading to symptoms of hirsutism, acne, irregular menses, and infertility. Multiple metabolic and cardiovascular risk factors are associated with PCOS, including insulin resistance, obesity, type 2 diabetes, hypertension, inflammation, and subclinical atherosclerosis. However, current treatments for PCOS are only moderately effective at controlling symptoms and preventing complications. This article describes how the physiological effects of major complementary and alternative medicine (CAM) treatments could reduce the severity of PCOS and its complications. Acupuncture reduces hyperandrogenism and improves menstrual frequency in PCOS. Acupuncture's clinical effects are mediated via activation of somatic afferent nerves innervating the skin and muscle, which, via modulation of the activity in the somatic and autonomic nervous system, may modulate endocrine and metabolic functions in PCOS. Chinese herbal medicines and dietary supplements may also exert beneficial physiological effects in PCOS, but there is minimal evidence that these CAM treatments are safe and effective. Mindfulness has not been investigated in PCOS, but it has been shown to reduce psychological distress and exert positive effects on the central and autonomic nervous systems, hypothalamic-pituitary-adrenal axis, and immune system, leading to reductions in blood pressure, glucose, and inflammation. In conclusion, CAM treatments may have beneficial endocrine, cardiometabolic, and reproductive effects in PCOS. However, most studies of CAM treatments for PCOS are small, nonrandomized, or uncontrolled. Future well-designed studies are needed to further evaluate the safety, effectiveness, and mechanisms of CAM treatments for PCOS.